Baseline-free delamination inspection in composite plates by synthesizing non-contact air-coupled Lamb wave scan method and virtual time reversal algorithm. (27th February 2015) - Liu, Zenghua; Yu, Hongtao; Fan, Junwei; Hu, Yanan; He, Cunfu; Wu, Bin
Abstract: In the paper, we combined air-coupled Lamb wave scan method and virtual time reversal (VTR) algorithm and proposed a composite baseline-free delamination inspection technique of composite plates. According to VTR algorithm, time reversal process is virtually performed through signal operations and the hardware manipulation for time reversal is not required. Baseline-free damage inspection can be achieved by comparing the first input actuation signal with the reconstructed final signal obtained by VTR algorithm. An air-coupled Lamb wave scan method combined with VTR-based probabilistic imaging algorithm is developed for delamination inspection of composite plates. Carbon fiber-reinforced composite plates with the delaminations of different shapes and sizes were experimentally tested. The testing results are well in accordance with the actual delamination locations and sizes as well as the results obtained with the commercial point-to-point immersion C-scan system.